DEVELOPING STUDENT WORKSHEET-BASED COOPERATIVE LEARNING MODEL FOR IMPROVING PROBLEM SOLVING ABILITY - Mayasari, Dian; Natsir, Irmawaty; Pagiling, Sadrack Luden; Taufik, Abdul Rachman (Universitas Papua, 2021)
Problem-solving ability is one of the essential skills for students in learning mathematics. This ability can be developed through teaching and learning activities using student worksheet-based cooperative model. However, these student worksheets are still rarely found in teaching and learning activities in the classroom, so this research aims to develop student worksheets based on cooperative learning models used to develop students' problem-solving abilities. The study used development research methods with ADDIE procedures, namely analysis, design, development, implementation, and evaluation. The test of the developedstudent worksheet was carried out at SMP Negeri 1 Merauke, using valid, practical, and effective categories. It is collecting data through interviews, observations, questionnaires, and tests. Data analysis was carried out by data reduction, presentation, and conclusion. This research produces student worksheets based on cooperative learning models to improve students' problem-solving abilities. The results of this study contribute to enriching teaching materials in the form of student worksheets for educators which can improve problem-solving skills.